2016
DOI: 10.1016/j.jaap.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of thermal decomposition of dihydroxybenzene isomers: Catechol, hydroquinone, and resorcinol

Abstract: In this study, dihydroxybenzene isomers such as catechol, resorcinol, and hydroquinone were used as models of volatiles from solid fuels to better elucidate the mechanism of the thermochemical conversion of solid fuels. These isomers were pyrolyzed in a two-stage tubular reactor with a residence time up to 3.6 s and temperature ranging from 650 to 950 °C. In total, 51 products were identified by online gas chromatography. The product distribution from the pyrolysis of the three isomers was quite different. p-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
2
25
0
Order By: Relevance
“…Here resorcinol showed a 15-fold increase in decarboxylation compared to the other two isomers. 19 C5H6 can further decompose to yield either C5H5 radicals and hydrogen or to acetylene (m/z 26) and propyne/allene (m/z 40). Cyclopentadienyl (C5H5) dissociates to propargyl (C3H3, m/z 39) and acetylene, as summarized in R4: 37,57 The C5H6 ms-TPES changes significantly with pyrolysis temperature and is analysed in detail below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here resorcinol showed a 15-fold increase in decarboxylation compared to the other two isomers. 19 C5H6 can further decompose to yield either C5H5 radicals and hydrogen or to acetylene (m/z 26) and propyne/allene (m/z 40). Cyclopentadienyl (C5H5) dissociates to propargyl (C3H3, m/z 39) and acetylene, as summarized in R4: 37,57 The C5H6 ms-TPES changes significantly with pyrolysis temperature and is analysed in detail below.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al employed a two-stage tubular reactor coupled with GC/MS detection to study the decomposition of benzenediols, and observed a 15-fold increase in CO2 production for resorcinol (RES) compared to the other two isomers. 19 They also reported a computed biradical driven reaction mechanism for the formation of CO2. However, their kinetics calculations suggested that decarboxylation is not feasible, at odds with their experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The micropyrolyzer reactors are usually coupled with gas chromatography (GC) techniques like GC-MS, GC-TOF-MS (time-of-flight mass spectrometer), or GC-FID ( Figure 2; Choi, Lee, Proano-Aviles, Lindstrom, Johnston, & Brown, 2017;Ronsse et al, 2012). U-shaped two-stage tubular reactors, separated by quartz wool, have been reported by Norinaga et al (Kousoku, Norinaga, & Miura, 2014;Norinaga et al, 2013;Qi et al, 2017;Yang et al, 2013;Yang, Appari, Kudo, Hayashi, & Norinaga, 2015;Yang, Furutani, Kudo, Hayashi, & Norinaga, 2016) for intrinsic gas-phase pyrolysis kinetic studies of cellulose and lignin model compound such as catechol, resorcinol, and hydroquinone pyrolysis. Pyroprobe reactors consist of a horizontal tubular reactor, wherein the sample is introduced using a quartz sample holder.…”
Section: Micro-tubular Reactorsmentioning
confidence: 99%
“…The p -benzoquinone product was only observed for hydroquinone ( p -benzenediol), while resorcinol ( m -benzenediol) produced significantly more CO 2 and C 5 hydrocarbons than the other two isomers. 17 Based on computations, a biradical reaction pathway was proposed. 18 By using in situ photoelectron photoion coincidence (PEPICO) methods, we found compelling spectroscopic evidence ( vide infra ) that the resorcinol decomposition mechanism is dominated by a retro-Diels–Alder reaction to produce CO 2 and C 5 H 6 isomers (R1) instead or it leads to two highly reactive ketenes species (R1).…”
Section: Introductionmentioning
confidence: 99%